Analisis Pengaruh Pajak Daerah Dan Rertribusi Daerah Terhadap PAD Kota /Kabupaten Di Provinsi Sumatera Utara - Sophia Hanum; Noni Rozaini (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2023)
This study aims to analyze the effect of local taxes and regional levies on city/regency local revenue (PAD) in North Sumatra province for the 2016-2021 period. The research method used is panel data regression method. This type of research uses quantitative methods and the data used is secondary data, namely data on local taxes, regional levies and PAD. The chosen research method is the fixed effect model. From the simultaneous test results, it was found that local taxes and regional levies have a significant effect on regional original income with a significance value of 0.000. From the results obtained, it is hoped that the city/regency governments in North Sumatra Province can make better use of the available sources of development financing funds to increase the amount of Local Own Revenue, especially those sourced from Regional Taxes and Regional Levies.